Furanosyl Oxocarbenium Ion Stability and Stereoselectivity1. Issue 39 (31st July 2014) - van Rijssel, Erwin R.; van Delft, Pieter; Lodder, Gerrit; Overkleeft, Herman S.; van der Marel, Gijsbert A.; Filippov, Dmitri V.; Codée, Jeroen D. C.
Abstract Lewis acid mediated substitution reactions using [D]triethylsilane as a nucleophile at the anomeric center of the four pentofuranoses, ribose, arabinose, xylose, and lyxose, all proceed with good to excellent stereoselectivity to provide the 1, 2‐cis adducts. To unravel the stereoelectronic effects underlying the striking stereoselectivity in these reactions we have mapped the energy landscapes of the complete conformational space of the oxocarbenium ions of the four pentofuranoses. The potential energy surface maps provide a detailed picture of the influence of the differently oriented substituents and their mutual interactions on the stability of the oxocarbenium ions and the maps can be used to account for the observed stereoselectivities of the addition reactions.